The neotropical flower-living genus Lenkothrips (Thysanoptera, Heterothripidae): three new species and an identification key - Cavalleri, Adriano; Mound, Laurence A. (Zootaxa, 2014)
Three new species are described in the South American genus of flower-feeding thrips, Lenkothrips De Santis & Sureda: L. mollinediae sp. n. from four species of Mollinedia (Monimiaceae) in Brazil and Ecuador; L. guaraniticus sp. n. and L. kaminskii sp. n. from Malpighiaceae in Brazil. An illustrated key to the five Lenkothrips species now recognized is provided.